Examination of variables that affect the efficacy of instructive feedback. (14th February 2017) - Haq, Shaji S.; Zemantic, Patricia K.; Kodak, Tiffany; LeBlanc, Brittany; Ruppert, Traci E.
Abstract : Instructive feedback is a procedure in which additional, nontarget stimuli are presented during instructional trials for students with a wide array of disabilities. This preliminary investigation examined whether participant behavior during instructive feedback, including attending and echoic behavior, altered the efficacy of instructive feedback for 2 children with autism. Results showed that participant behavior during instructive feedback related to training outcomes for both participants and treatment modifications based on participant behavior influenced acquisition. Future directions of research and implications for practice are discussed.